Augmenting Function with Value: An Exploration of Reasons to Engage and Disengage from Music Listening. (29th June 2021) - Krause, Amanda E; Glasser, Solange; Osborne, Margaret
Investigations of music in everyday life are dominated by a functional perspective, drawn from work using the theory of Uses and Gratifications. In so doing, we may have neglected to fully appreciate the value people place on music listening. Therefore, the present study considered if, and why, people value music listening and probed instances when they may not want to listen to music in everyday life. A sample of 319 university students residing in Australia (76.50% female, M age = 20.64) completed an online questionnaire, on which they were asked to provide short responses to open-ended questions directly addressing two research questions. Inductive thematic analysis yielded 13 themes synthesizing how participants valued listening to music, such as appreciation, emotion, time and engagement, cognitive factors, and mood regulation. Reasons for not listening to music were summarized by eight themes dominated by interference with activities that required focus or concentration, followed by environmental context, affective responses, music engagement and inversely, a preference for silence or other auditory stimuli. Fifteen percent of participants stated there was never a time they did not want to listen to music. The findings provide a novel perspective on the value of music listening beyond that considered by uses and gratifications with regard to the function of listening to music in everyday life.